PENDAMPINGAN ORANG TUA UNTUK MENANGGULANGI GENG ANAK DI JALAN DWIJAYA KEBAYORAN LAMA JAKARTA - Tarjiah, Indina; Handayani, Mardiana (Universitas Muhammadiyah Jakarta, 2018)
ABSTRACTParents’ assistance to overcome child gangs on Dwijaya Kebayoran Lama street in South Jakarta. The aim of the researchers was to raise this title because they wanted to be more deeply aware of the assistance of parents in tackling child gangs that had already taken place and how parents could overcome them. This study uses an ethnographic qualitative research design because the design of this study involves a group, community, or gang, and this study uses a long time due to an in-depth observation of the group. Research location in Jalan Dwijaya RT 10 RW 11 Kelurahan Kebayoran Lama, South Jakarta Province. The results of the study show that parental assistance is needed in overcoming a large gang, assisting parents through communication with children. Parents educate their children early through religious education and social order in the community so that children can adapt to the environment easily without the need for help from parents. The gang of children is not a terrible gang if there has been an early handling of assistance from their parents. Because no matter how far the child is playing with friends, the game is never escaped from the parents' perspective even though the parent is busyKeywords: Parents’ assistance, child gangs, ethnographic researchABSTRAKPendampingan orangtua untuk menanggulangi geng anak di jalan Dwijaya Kebayoran Lama Jakarta Selatan. Tujuan peneliti mengangkat judul ini karena ingin lebih dalam lagi mengetahui pendampingan orangtua dalam menanggulangi geng anak yang sudah marak terjadi dan bagaimana orangtua dapat mengatasinya. Penelitian ini menggunakan desain penelitian kualitatif etnografi karena desain penelitian ini melibatkan sebuah kelompok, masyarakat, maupun geng dan penelitian ini menggunakan waktu yang lebih lama dikarenakan pengamatan yang mendalam kepada kelompok tersebut. Lokasi penelitian di Jalan Dwijaya RT 10 RW 11 Kelurahan Kebayoran Lama Provinsi Jakarta Selatan. Hasil penelitian menunjukkan bahwa pendampingan orangtua sangat dibutuhkan dalam menanggulangi terjadinya sebuah geng yang besar, pendampingan orangtua melalui komunikasi kepada anak. Orangtua mendidik anaknya sejak dini melalui pendidikan agama dan ketertiban sosial di masyarakat sehingga anak dapat beradaptasi kepada lingkungan dengan mudah tanpa harus adanya bantuan dari orangtua. Geng anak tidaklah menjadi sebuah geng yang mengerikan jika sejak dini sudah ada penanganan pendampingan dari orangtuanya.Kata kunci: Pendampingan orangtua, geng anak, penelitian etnografi